1996
DOI: 10.1093/oxfordjournals.humrep.a019434
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness as a predictor of pregnancy after in-vitro fertilization but not after intracytoplasmic sperm injection

Abstract: An ultrasonographic evaluation of the endometrium was performed in 158 patients undergoing ovarian stimulation for an in-vitro assisted reproduction programme. Endometrial thickness was evaluated in 109 patients undergoing in-vitro fertilization (IVF) for female indications and in 49 patients undergoing intracytoplasmic sperm injection (ICSI) for male indications. The maximal endometrial thickness was measured on the day of human chorionic gonadotrophin (HCG) administration by longitudinal scanning of the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 16 publications
2
56
2
Order By: Relevance
“…21,22 In accordance with our results, Rinaldi et al found that, unlike IVF cycles, endometrial thickness could not predict ICSI success as a result of higher fetilization ratio. 23 Our study showed that, at the other end of the spectrum, patients whose endometrium thinner than 6 mm achieved 36.4% CPR. Similiarly, Bozdag, and colleagues reported %35 CPR in patiens undergone ICSI whose endometrial thickness below 7 mm.…”
Section: Discussionmentioning
confidence: 50%
“…21,22 In accordance with our results, Rinaldi et al found that, unlike IVF cycles, endometrial thickness could not predict ICSI success as a result of higher fetilization ratio. 23 Our study showed that, at the other end of the spectrum, patients whose endometrium thinner than 6 mm achieved 36.4% CPR. Similiarly, Bozdag, and colleagues reported %35 CPR in patiens undergone ICSI whose endometrial thickness below 7 mm.…”
Section: Discussionmentioning
confidence: 50%
“…Despite the existence of quite a few published studies, the prognostic value of ultrasonographic endometrial thickness measurements (and other parameters) in predicting implantation and pregnancy rates remains controversial. Some investigators have demonstrated a positive correlation between endometrial thickness and pregnancy rates [1][2][3][4][5][6][7][8]11] while others have not found such an association [9,10,[12][13][14], or only in association with other parameters [15,16]. However, these differences may be in part attributed to different patient populations, stimulation protocols used or measurement timing.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that this parameter is important for predicting the outcome of In Vitro Fertilization (IVF) cycles [1][2][3][4][5][6][7][8], other studies have failed to show such a positive relationship [9][10][11][12][13][14]. In a third category of studies the endometrial thickness was related to the IVF outcome, but only in correlation with other parameters [15,16]. Different thresholds of endometrial thickness were suggested as essential for successful implantation and most demonstrated that no pregnancy was established when the thickness of the pre-ovulatory endometrium was <6 mm [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple studies that have supported or refuted the relationship between endometrial features such as thickness, length or pattern and the implantation rate (Bassil,2001;Kovacs et al,2003;Richter et al,2007;Zhang et al,2005;Rinaldi et al,1996). The data regarding the role of endometrial thickness as a predictor of implantation outcomes is still controversial.…”
Section: The Role Of Endometrial Structurementioning
confidence: 99%
“…The data regarding the role of endometrial thickness as a predictor of implantation outcomes is still controversial. Most of the authors suggested that there is a trigger of endometrial thicknesses correlating with a significant reduction in the implantation rate (Bassil,2001;Weissman et al,1999;Rinaldi et al,1996). Some investigators tried to evaluate the endometrial pattern on the day of hCG administration, the day of oocyte retrieval or the day of embryo transfer and find some predicting markers of successful embryo implantation (Dickey et al,1992;Rashidi et al,2005), but the results did not show any statistically significant results.…”
Section: The Role Of Endometrial Structurementioning
confidence: 99%